Repeatability of the superovulatory response in embryo production in vivo with a modified pFSH protocol in Australian Merino sheep - Gómez-Ceruti, Marcela (2023)
The study evaluated the repeatability of the superovulatory response in 12 Australian Merino ewes during the breeding season in one (G1), three (G2), and four (G3) consecutive years. A modified protocol was used based on 200 mg pFSH in eight decreasing doses (12-h intervals) and supportive strategies such as changing the CIDR at day 7, spraying the horns with heparinized saline during the procedure, and use of Flunixin Meglumine. No significant differences were found in the total number of structures recovered during the years of application of the superovulation protocol (G1=8±2, G2=18±3, G3=19±4; p>0.05). High repeatability was observed, both for the total number of embryos and for the number of transferable embryos in G2 and G3. Superovulatory treatment for 3 and 4 successive years did not affect the efficacy of embryo retrieval.